Sweden : Financial Sector Assessment Program Update: Technical Note on Reviewing the Systemic Liquidity Risk Management Framework. (IMF Staff Country Reports; Country Report ;, 2011)
The Swedish banking system faced a severe liquidity strain during the global financial crisis owing to their extensive reliance on global wholesale funding to support expansion in their credit operations. This note gives a detailed review on the recommendations made in the Financial Sector Assessment Program (FSAP) Update in the area of systemic liquidity risk management, especially in relatively weak areas and some aspects of Riksbank's domestic liquidity toolkit. But it does not cover a range of issues on emergency liquidity assistance to individual institutions.